Tuning the Magnetic Anisotropy of Lanthanides on a Metal Substrate by Metal–Organic Coordination. Issue 35 (18th July 2021) - Parreiras, Sofia O.; Moreno, Daniel; Cirera, Borja; Valbuena, Miguel A.; Urgel, José I.; Paradinas, Markos; Panighel, Mirco; Ajejas, Fernando; Niño, Miguel A.; Gallego, José M.; Valvidares, Manuel; Gargiani, Pierluigi; et al.
Abstract: Taming the magnetic anisotropy of lanthanides through coordination environments is crucial to take advantage of the lanthanides properties in thermally robust nanomaterials. In this work, the electronic and magnetic properties of Dy‐carboxylate metal–organic networks on Cu(111) based on an eightfold coordination between Dy and ditopic linkers are inspected. This surface science study based on scanning probe microscopy and X‐ray magnetic circular dichroism, complemented with density functional theory and multiplet calculations, reveals that the magnetic anisotropy landscape of the system is complex. Surface‐supported metal–organic coordination is able to induce a change in the orientation of the easy magnetization axis of the Dy coordinative centers as compared to isolated Dy atoms and Dy clusters, and significantly increases the magnetic anisotropy. Surprisingly, Dy atoms coordinated in the metallosupramolecular networks display a nearly in‐plane easy magnetization axis despite the out‐of‐plane symmetry axis of the coordinative molecular lattice. Multiplet calculations highlight the decisive role of the metal–organic coordination, revealing that the tilted orientation is the result of a very delicate balance between the interaction of Dy with O atoms and the precise geometry of the crystal field. This study opens new avenues to tailor the magnetic anisotropy and magnetic moments of lanthanide elements on surfaces. Abstract : The electronic and magnetic properties of Dy metal–organic networks are inspected on a coinage surface. It is revealed that the coordination environment re‐orientates the easy axis of magnetization and tunes the magnetic anisotropy of Dy centers compared to isolated atoms, thus opening new avenues for tailoring the magnetic properties of lanthanides in 2D materials.